2005
DOI: 10.1002/app.22341
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization kinetics of nitrile rubber/layered clay nanocomposites

Abstract: Cure kinetic studies on nitrile rubber(NBR)-layered clay nanocomposites, prepared by a melt mixing process, was investigated using a cure rheometer and differential scanning calorimeter (DSC). The characterization of the structure of the nanocomposites of uncured and cured samples was performed using X-ray diffraction. The results showed that the interlayer spacing of cured nanocomposites was smaller than that of the uncured sample due to partial removal of organoclay from the interlayer spacing. The cure char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 31 publications
8
69
0
1
Order By: Relevance
“…These results suggest an increase of the curing rate promoted by the quaternary alkylammonium salt present as the intercalant for the organoclay. Similar results have been observed by other authors [9,28] . The maximum torque also increased with the presence of clay.…”
Section: Curing Parameters and Physico-mechanical Propertiessupporting
confidence: 93%
See 2 more Smart Citations
“…These results suggest an increase of the curing rate promoted by the quaternary alkylammonium salt present as the intercalant for the organoclay. Similar results have been observed by other authors [9,28] . The maximum torque also increased with the presence of clay.…”
Section: Curing Parameters and Physico-mechanical Propertiessupporting
confidence: 93%
“…The curing process has also been claimed by several authors as a very important factor governing the exfoliation/intercalation degree in rubber/clay nanocomposites. Nah et al [9,16] observed a shift of the X-ray diffraction peak related to the basal interspacing of the organoclay towards higher 2θ values after curing the melt blended nitrile rubber-clay system. The authors have suggested that part of the intercalated component in the clay were squeezed out from the layer, giving rise to some clay aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o grau de conversão (  ) em uma reação de cura pode ser determinada a partir das propriedades viscoelásticas medidas através de um reômetro (CHOUGH e CHANG, 1996;LOPEZ-MANCHADO et al, 2003;CHOI et al, 2005). O valor de  pode ser definido pela Equaçao 1:…”
Section: Cinética De Vulcanizaçãounclassified
“…Most previous studies about the vulcanization kinetic of RCNs indicted that addition of OMC would considerably increase curing rate and crosslinking density of various rubber compounds, including NR [24,25], ENR [26], BR [27,28], SBR [29], EAR [30], NBR [31], and NBR/SBR blend [32]. On the other hand, some studies [12,33] on EPDM/OMC systems shown that addition of OMC prolonged the optimum curing time and reduced the cross-linking density of the composites.…”
Section: Effects Of Omc On the Curing Processmentioning
confidence: 99%